FORMATION OF READINESS TO FUTURE RESCUERS’ PROFESSIONAL COMMUNICATION OF STATE SERVICE OF EMERGENCY SITUATIONS (Journal of Information Technologies in Education (ITE), 2013)
The essence, the content and the forming model of readiness to future rescuers’ professional communication of State Service of Emergency Situations in the process of their training in the institute of higher education have been considered in the article using information-educational environment and design technology training «Web quest».
Keywords: professional communication readiness; competence approach; communication; professional communication